Free Radical Scavenging Activities of Methanol Extract and Fractions of Picralima nitida (Apoceanacea) - Osayemwenre Erharuyi; Abiodun Falodun (Journal of Applied Sciences and Environmental Management)
Picralima nitida commonly called picralima or pile plant is a tree or shrub with widely varied applications in West African folk medicine. The study evaluated the free radical scavenging activities of the crude methanol extract of Picralima nitida root bark and its various fractions. The methanol extract of P. nitida and its fractions were subjected to in vitro antioxidant evaluation using the DPPH free radical scavenging method. The IC-50 values for the percentage radical scavenging effects for the extract and fractions were determined. Statistical significance between the IC-50 values of the extract/fractions and that of ascorbic acid (standard) was determined using regression analysis. The crude extract has IC-50 value for radical scavenging activity of 5μg/mL which was significantly higher than that of ascorbic acid (2.55μg/mL). However, the percentage inhibition of the crude extract and ascorbic acid (standard) showed no significant difference. Picralima nitida has the potential for use as natural plant antioxidants in preventing against free radical damage.